Comparative Economic Analysis of Input Application of Large Cardamom in Kalimpong and Darjeeling District of West Bengal - Dawjam Bhutia; Anmol Giri; Dukchuk Tamang; Md. Hasrat Ali (Archives of Current Research International, 2025)
A comparative analysis of the production, cost structures, and profitability of large cardamom (Amomum subulatum Roxb.) is a high-value perennial spice crop predominantly grown in the Eastern Himalayan region, including Nepal, Bhutan, and northeastern India. This crop holds significant economic importance for smallholder farmers in hilly areas due to its lucrative market demand both domestically and internationally. The present study undertakes a comparative economic analysis of large cardamom cultivation in Kalimpong and Darjeeling districts of West Bengal, India, with a focus on input use, labour requirements, cost structure, yield, and profitability over multiple years. The research is based on primary data collected through a systematic farm-level survey of 50 sample growers in the Gorubathan block of Kalimpong and 50 sample growers from Rangli-Rangliot block of Darjeeling, using multistage purposive sampling and random sampling techniques. Data on labour days, input quantities, costs, yield, and returns were collected and analyzed using both descriptive and inferential statistical methods to understand inter-annual and inter-regional variations. Results indicate that while Kalimpong shows higher productivity and gross returns per hectare, it is associated with relatively higher input and labour costs compared to Darjeeling, where resource use efficiency is greater. Across both regions, the third year of cultivation consistently recorded the highest yield and returns, followed by a slight decline in the fourth year, reflecting the perennial nature of the crop and its production cycle. The study also highlights the socio-economic benefits of large cardamom cultivation, particularly its role in promoting gender equality through uniform wage structures and women’s active participation in farming activities. The findings underscore the economic viability and resilience of large cardamom cultivation under the agro-climatic conditions of the Eastern Himalayas. The study recommends targeted policy interventions to strengthen market linkages, reduce supply chain inefficiencies, and support smallholder farmers to enhance profitability and sustainability in large cardamom production. This research contributes valuable insights for agronomists, policymakers, and development practitioners aiming to boost spice-based livelihoods and rural development in hill regions.